THE GROWTH AND DEVELOPMENT OF WEALTH FROM THE ISLAMIC SYSTEM: التنمية و التطور في الأموال من منظوم الإسلام - Muhammad Fahroni Hamsan; Isman Isman; Imron Rosyadi; Rania Mahmoud ELSakhawy; Ali Rabbani (Universitas Muhammadiyah Surakarta, 2023)
It is very important for a Muslim in everything to be guided or pay attention to Islamic rules so as not to fall into things that are prohibited by religion. Including in economic activities should pay attention to the rules in muamalah fiqh. The purpose of writing this article is to explain to the public what should not be done when someone is doing activities in developing property. The method used in this writing is the library research method with a qualitative descriptive approach. The result: among the rules of Islamic economics in the development of wealth is that buying and selling should not contain things that are prohibited or detrimental such as usury, fraud, theft and so on.